Crisis of Professional Journalism in the Transitional Society of Serbia - Milutinović, Irina R. (Sociološki pregled, 2019)
Processes of media transition in the Republic of Serbia, triggered by the political changes in 2000, have been unfolding through harmonization with the EU regulatory framework. These processes have been strongly determined by the development in the information and communication field, too. The aim of this research is to discuss the state of professional journalism two decades after the beginning of media transition in Serbia. Mechanisms of self-regulation and the Code of Ethics are perceived as a tool for the emancipation of the journalism profession in a fragile democratic environment. Using the scientific method, the research shows why self-regulatory instruments have failed to ensure the integrity of the journalistic profession in the process of media transition.
Keywords: journalism; code of ethics; profession; media transition; Republic of Serbia